184k views
4 votes
What is the solution ?

What is the solution ?-example-1
User Nakres
by
5.1k points

1 Answer

6 votes

Answer:

x = - 2

y = - 4

Explanation:

The given equations are:


$ 4x - 3y = 4 \hspace{10mm} \hdots (1) $


$ x - y = 2 \hspace{12mm} \hdots (2) $

To solve this system of equations, we eliminate one variable.

Let us eliminate the variable 'x' here.

To do that multiply Equation (2) by 4.

⇒ 4x - 4y = 8 . . . (3)

The co - effecients of x in both the equations are now same. Subtract the two equations.

(1) - (3) = -3y - (-4y) = 4 - 8

⇒ - 3y + 4y = - 4

y = - 4

Substituting the value of 'y' in Equation (2) we get:

x - (-4) = 2

⇒ x + 4 = 2

x = - 2 which is the required answer.

Hence (x, y) = (-2, - 4) is the solution to the above system of equations.

User Armando Ramirez
by
5.7k points